The The Effect of Augmented Reality Virtual Try-On on Purchase Intention Through the Mediation of Perceived Enjoyment - Ni Made Prayogi Wahyu Sutarjana; Ni Wayan Ekawati Ekawati (LPPM STIE Kasih Bangsa, 2025)
Abstract. The shift in consumer behavior from offline to online platforms has significantly accelerated the growth of e-commerce in Indonesia, fundamentally transforming how businesses interact with their customers. Luxcrime, a local cosmetic brand, has responded to this digital evolution by integrating an augmented reality (AR) virtual try-on feature through the Shopee marketplace. This feature is a key component of the brand's digital marketing strategy aimed at enhancing customer engagement, interactivity, and purchase decision-making processes. This study investigates the mediating role of perceived enjoyment in the relationship between AR virtual try-on experiences and consumers' purchase intention toward Luxcrime products on Shopee, specifically in Denpasar City. A total of 100 respondents were surveyed using offline questionnaires with purposive non-probability sampling. The research adopts a combined theoretical framework—Stimulus-Organism-Response (SOR) theory and the Technology Acceptance Model (TAM)—to better understand consumer psychological responses and behavioral outcomes in digital environments. The collected data were analyzed using path analysis via SPSS version 26.0. The results show that all hypotheses are supported: AR virtual try-on has a significant and positive impact on both perceived enjoyment and purchase intention. Furthermore, perceived enjoyment plays a partial mediating role between AR try-on and purchase intention, indicating that enjoyment enhances the persuasive power of virtual product interactions. The study concludes that AR features should not only serve a functional purpose but also evoke positive emotional experiences to maximize their impact. Luxcrime is advised to continue improving the quality, realism, and interactivity of its AR features to increase consumer satisfaction and conversion rates in a competitive digital marketplace.